Kecemasan Pedagang Unggas Tentang Wabah Penyakit Flu Burung Di Pasar Tunggorono Jombang - Kurniawati Kurniawati (Akademi Keperawatan Dharma Husada Kediri, 2015)
Avian influenza is one of an infectious disease caused by influenza virus is transmitted by Avian influenza humans. This incident resulted in anxiety for the chicken market traders in tunggorono Jombang. Levels of anxiety can be clarified into 5 levels ie no anxiety, mild anxiety, worry is, severe anxiety, and anxiety heavy (panic).The purpose of this study to describe the anxiety level of poultry traders in the market Tunggorono Jombang.The study design is descriptive. Respondents who studied the poultry traders in the market Tunggorono Jombang. Sampling with a total sampling technique, a large sample of 30 respondents. Methods of observation and data collection by questionnaire. Analyze data using descriptive analysis formula is a frequency distribution. The result showed that the level of axienty in the market Tunggorono poultry traders as much as 53,4% in the level of anxiety being.Anxiety levels of poultry traders about avian influenza outbreak in Jombang Tunggorono market is the level of anxiety is. This needs to be done counseling or health education to lower levels of anxiety. Key words : Anxiety, Avian influenza